Regional atrophy, cellular plasticity, and regenerative potential in irradiated murine salivary glands - Inga Solgård Juvkam; Olga Zlygosteva; Olaf Joseph Franciscus Schreurs; Nina Jeppesen Edin; Hilde Kanli Galtung; Eirik Malinen; Tine Merete Søland (Acta Oncologica)
Background and purpose: Radiotherapy of head and neck cancer may cause detrimental late side effects such as fibrosis and hyposalivation. We investigated mouse salivary glands after fractionated irradiation, with the aim to elucidate cellular plasticity and potential regeneration.